Sandstone Trade and Personal Networks. Considering on Networks in the Context of an Analysis of a Transregional Exchange of Material and Knowledge in the Northwest German and Dutch Region in the Early Modern Age - Neuser, Wiebke (De Gruyter, 2021)
Das Kapitel Sandstone Trade and Personal Networks. Considering on Networks in the Context of an Analysis of a Transregional Exchange of Material and Knowledge in the Northwest German and Dutch Region in the Early Modern Age erschien in Innovation in der Bauwirtschaft Innovation in the Building Industry auf Seite 315.